2017
DOI: 10.1186/s12974-017-0996-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-NF155 chronic inflammatory demyelinating polyradiculoneuropathy strongly associates to HLA-DRB15

Abstract: BackgroundThe aim of the research is to study the human leukocyte antigen (HLA) class II allele frequencies in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) associated with anti-neurofascin 155 (NF155) antibodies.MethodsThirteen anti-NF155+ and 35 anti-NF155 negative (anti-NF155neg) CIDP patients were included in a case-control study. The frequencies of the DRB1 HLA allele were analyzed in all patients while DQ frequencies were only studied in patients sharing the DRB1*15 allele. In silico H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…By contrast, extensive proximal nerve hypertrophy and pronounced CSF protein elevation, suggesting severe inflammation and/or edema of nerve roots, is unique to this condition, but is difficult to explain solely by IgG4 antibody functions. Recently, a strong association of certain human leukocyte antigen ( HLA ) class II alleles with NF155 + CIDP was reported in a European series, suggesting HLA class II‐restricted T‐cell involvement. These observations prompted us to clarify the CSF cytokine profile in patients with IgG4 NF155 + CIDP to elucidate the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, extensive proximal nerve hypertrophy and pronounced CSF protein elevation, suggesting severe inflammation and/or edema of nerve roots, is unique to this condition, but is difficult to explain solely by IgG4 antibody functions. Recently, a strong association of certain human leukocyte antigen ( HLA ) class II alleles with NF155 + CIDP was reported in a European series, suggesting HLA class II‐restricted T‐cell involvement. These observations prompted us to clarify the CSF cytokine profile in patients with IgG4 NF155 + CIDP to elucidate the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In a collaborative study we found that anti‐NF155+ CIDP patients associates with HLA‐DRB15 20 times more frequently than in seronegative CIDP (Martinez‐Martinez and coworkers, unpublished observation) (Martinez‐Martinez et al, ) further supporting the idea that patients with these antibodies constitute a distinct subset of CIDP.…”
Section: Antibodies To Paranodal Glycoproteinsmentioning
confidence: 70%
“…Very recently, European researchers reported that the DRB1*15 alleles ( DRB1*15:01 and DRB1*15:02 ) were present in 10 out of 13 anti‐NF155 antibody‐positive CIDP patients and in just five out of 35 anti‐NF155 antibody‐negative CIDP patients (77% vs 14%; odds ratio 20, 95% confidence interval 4.035–99.13) . Strong relationships between particular human leukocyte antigen class II alleles and other IgG4‐mediated autoimmune diseases have been reported, such as anti‐muscle‐specific tyrosine kinase antibody myasthenia gravis ( DR14‐DQ5 haplotype), leucine‐rich glioma inactivated 1 encephalitis ( DRB1*07:01–DQB1*02:02 haplotype) and thrombotic thrombocytopenic purpura ( DRB1*11 ), suggesting that these disorders have common pathomechanisms.…”
Section: Characteristics Of Anti‐nf155 Antibody‐positive Cidpmentioning
confidence: 99%